Recognizing the vulnerability of Generation Z to economic and social risks - Blagica Novkovska; Gordana Serafimovic (UTMS Journal of Economics, 2018)
Generation Z, known also as 'Net generation' and 'Digital natives', is of particular interest for researchers do to its specifics originating from the changes caused in the everyday's live by the new technologies. This cohort is known to be highly vulnerable to several economic and social risks, depending on the characteristics of the society where they live. In this paper the socio-economic situation of youth in some small countries with different level of development is studied. Particular importance is paid to the criminality as a risk factor for Generation Z. The case of Macedonia has been studied in details, using the relevant data for the period from 2007 to 2016. Based on the use of a multivariate linear regression model it has been found that the criminality is strongly related to the size of NEET (part of the cohort that is Not in Education, Employment or Training).
Keywords: C22; C52; E24; I24; J29; 330; youth; NEET; poverty; labour market transitions